Customer Loyalty of Ibu Titi Laundry Post-Demi with Promotion, Location and Service Variables Moderated by Company Logo - Willyan Bagus Alamsjah; Suyanto Suyanto (Universitas Negeri Makassar, 2023)
Laundry needs are dominated not only by the household sector, but also by workers and students who tend to live in temporary accommodation such as contract houses, boarding houses, or rented accommodation. Such is the importance of laundry that the business is growing rapidly. In the past, the laundry business was mainly run by hotels, but now it can be used by people with capital and the general public. This post-pandemic oriented research was conducted at Bu Titi Laundry by taking 28 respondents from the population as the research sample. The primary data was collected by distributing questionnaires with response options in the form of an ordinal scale, namely strongly disagree to strongly agree with five scales. The research was conducted quantitatively using WarpPLS 7.0 analysis with hypothesis testing using t-test and sig 0.05. This study shows that promotion and location have a positive and significant effect on customer loyalty, but service is not significant for customer loyalty. As a moderator, the logo had no effect in moderating loyalty through promotion, location and service.